Ability Of Madrasah Ibtidaiyah Students In Completing Multiplication Calculation Operations Using The Lattice Method - Sita Husnul Khotimah; Nining Yuningsih (Edukasiana: Journal of Islamic Education, 2025)
This study aims to explore the application of the lattice method in improving students' ability to complete multiplication operations in class V of MI Tarbiyatul Islamiyah Jagakarsa, South Jakarta, as well as to describe the advantages and disadvantages of this method. The approach used in the study is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The research subjects consisted of 31 students of class V. Data analysis was carried out by data reduction steps, data presentation, and conclusion drawing using models from Miles and Huberman. The results indicate that the application of the lattice method makes it easier for students to understand the concept of multiplication through visualization in the form of grids. Students appear more excited, thorough, and confident when solving multiplication problems when compared to traditional methods. The learning outcome data showed a significant increase: the number of students who achieved complete scores increased from 5 students to 16 students, while students who did not complete decreased from 17 to 5 students. These findings are supported by interviews with teachers and students who stated that the lattice method is more interesting, structured, and can reduce errors in recording numbers or summation.